Career movements of graduates of UPV Master's Program (1976-1986) - Tayo, Gilma T.
To assess the relevance and effectiveness of UPV Graduate Programs, in terms of career mobility of its graduates, questionnaires were mailed to UPV Master's Degree graduates of 1976 up to the present. From 233 responses it was shown that 70% were promoted after acquiring their master's degrees. The respondents considered degree as the major factor for their promotion, followed by work attitude and intelligence. Of those that were given priority of promotion over other master's degree holders in their companies, 59% believed their UP degree gave them the edge.